PENGARUH PERSEPSI LINGKUNGAN BISNIS INTRAPRENUER DAN RISK PROPENSITY TERHADAP NIAT KEWIRAUSAHAAN (STUDI TERHADAP KEPALA CABANG LEASING ABC) - Elissa Dwi Lestari (Ultima Management : Jurnal Ilmu Manajemen, 2019)
In the midst of a business environment that is full of uncertainties, organizations must always be dynamic and improve entrepreneurship as a form of strategic response. Aims of this study are to explain the influence of perceived external business environment (dynamic, munificence, hostile and complex) as the organization external factor, and the tendency of individuals to take risks to entrepreneurial intentions at the level of individual branch heads. The object of this research is ABC Leasing which is experiencing environmental uncertainty as a result of the declining market of certain brand motorcycles as their main target of financing. The study was conducted based on 144 data collected from branch heads and Post Head Leasing ABC throughout Indonesia. Data analysis was analyzed using multiple regression to see the effect of perceived external business environment variables and risk propensity on entrepreneurial intentions. The results showed that the perceived of a dynamic business environment, the perceived of environmental munificence, the perceived of a complex environment and the tendency to take risks influence the formation of entrepreneurial intentions while the perception of a hostile environment has no significant effect.